Omental infarction in an obese 10-year-old boy - Katerina Kambouri; Stefanos Gardikis; Alexandra Giatromanolaki; Aggelos Tsalkidis; Efthimios Sivridis; George Vaos (MDPI AG, 2011)
Primary omental infarction (POI) has a low incidence worldwide, with most cases occurring in adults. This condition is rarely considered in the differential diagnosis of acute abdominal pain in childhood. Herein, we present a case of omental infarction in an obese 10-year-old boy who presented with acute abdominal pain in the right lower abdomen. The ultrasound (US) examination did not reveal the appendix but showed secondary signs suggesting acute appendicitis. The child was thus operated on under the preoperative diagnosis of acute appendicitis but the intraoperative finding was omental infarct. Since the omental infarct as etiology of acute abdominal pain is uncommon, we highlight some of the possible etiologies and emphasize the importance of accurate diagnosis and appropriate treatment of omental infarction.